Analisis Perbandingan Kinerja Keuangan Bank Syariah dan Bank Konvensional - Ash-Shiddiqy, Muhammad (Risalah Iqtishadiyah, 2023)
Banking institutions are the core of the financial system of every country. The types of banks in Indonesia are divided into two types of banks, namely banks based on conventional principles and banks based on sharia principles. The main difference between these two types of banks is in terms of price determination, both selling and buying prices. This research aims to determine and analyze the financial performance of sharia banking when compared with conventional banking for each financial ratio, analyzing the performance of sharia banking compared to conventional banking as a whole. This research uses descriptive qualitative methods with primary and secondary data approaches. Primary data is data obtained directly through interviews. Meanwhile, secondary data is data obtained through observation and documentation. The results of this research show that the differences between conventional banks and Sharia banks can be seen from the differences in philosophy, concept of managing customer funds, obligations to manage zakat, and organizational structure. Where Conventional Banks invest in halal and haram businesses, while Sharia Banks invest in businesses that are halal and in accordance with sharia principles sourced from the Qur'an and AL Hadith.